Relative age is associated with male soccer dropout - Delorme, N.; Boiche, J.; Raspaud, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The purpose of this study is to examine the birthdates distribution of French male soccer players who ceased their participation, so as to test whether the Relative Age Effect (RAE) is related to the dropout behaviour. We hypothesize that young players born late in the competitive year would be over-represented in the dropout sample. Conversely, because of their relative age and its associated advantages, the young players born early in the year should be under-represented in this sample. Methods At the end of the 2007-2008 season, the birthdates of the French male players (n = 363,590) licensed during the 2006-2007 season and that had not reiterated their licence during the following season were collected through the database of the French Soccer Federation (FSF). We waited until the end of the 2007-2008 season to collect the data, in order to avoid considering as dropout some players that took their licence while the new season had already begun. For each of the 7 age categories distinguished by the FSF, the players` birthdates were classified into 4 quarters. As the cut-off date has changed in France, players born before 1982 were classified from Q1 (August-October) to Q4 (May-July), whereas those born in 1982 and after were classified from Q1 (January-March) to Q4 (October-December). Then, a chi square test was carried out to determine whether the observed distribution by quarter significantly differed from the theoretical distribution. The theoretical distribution was calculated from the corresponding population of licensed players, using weighted mean scores. Results An over-representation of players born in the last two quarters was found among dropouts, from the less than 9 to the less than 18 age categories, whereas the players born during the first two quarters were under-represented. No significant difference between the theoretical and observed distribution appeared concerning the less than 7 and adult categories. Discussion These results confirm that the RAE can act as a sport dropout factor from the less than 9 to the less than 18 age categories. For the players born in Q4, the differences in physical attributes and the subsequent reduced opportunities to play, associated with lowered self-worth perceptions and perceived competence, are likely to lead to higher dropout rates. Concerning the less than 7 category, the absence of effect can be explained by two elements. First of all, in this category, the differences in terms of physical attributes remain modest. Next, it must be outlined that the FSF does not organize official competition for them. Thus these players are less likely to be confronted to situations of failure or inferiority. Finally, a distribution conform to the one observed among the whole population of licensed adult players was observed among adult dropout players. This result is coherent with past studies having shown that RAE gradually declines with age.